2012
DOI: 10.1164/rccm.201106-1027oc
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Regulates Epithelial Cell Response to Aspergillus and Resultant Pulmonary Inflammation

Abstract: Rationale: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) alter epithelial cell (EC) interactions with multiple microbes, such that dysregulated inflammation and injury occur with airway colonization in people with cystic fibrosis (CF). Aspergillus fumigatus frequently colonizes CF airways, but it has been assumed to be an innocent saprophyte; its potential role as a cause of lung disease is controversial. Objectives: To study the interactions between Aspergillus and EC, and the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 46 publications
(58 reference statements)
0
73
0
3
Order By: Relevance
“…Consistent with this, work with CF cell lines and cells cultured from the airways of CF mice indicate that CF airway cells are comparatively more sensitive to apoptotic induction by drugs (46,47), fungal spores (48), and cigarette smoke (49). Conversely, Gottlieb and colleagues (50) reported that mutant CFTR confers resistance to a proapoptotic drug.…”
Section: S Aureusmentioning
confidence: 79%
“…Consistent with this, work with CF cell lines and cells cultured from the airways of CF mice indicate that CF airway cells are comparatively more sensitive to apoptotic induction by drugs (46,47), fungal spores (48), and cigarette smoke (49). Conversely, Gottlieb and colleagues (50) reported that mutant CFTR confers resistance to a proapoptotic drug.…”
Section: S Aureusmentioning
confidence: 79%
“…Studies provide further support for the concept that A. fumigatus may not be an innocent bystander in CF lung disease. Chaudhary and colleagues used a combination of in vitro and in vivo studies to demonstrate that A. fumigatus uptake by CFTR-deficient cells is reduced, but that epithelial cell apoptosis after exposure to A. fumigatus is increased (11). This raises a question concerning whether CFTR plays a role in intracellular uptake of A. fumigatus as previously demonstrated for P. aeruginosa (12).…”
Section: Cystic Fibrosis Microbiologymentioning
confidence: 93%
“…Direct interaction between the CFTR protein and pathogens has been previously suggested, where CFTR serves as a receptor for Salmonella typhi [108] and P. aeruginosa [109,110] when expressed on intestinal or airway epithelial cells, respectively. Moreover, A. fumigatus spores are readily ingested by airway epithelial cells and the uptake and killing of conidia are both impaired in epithelial cells lacking CFTR [111]. The bronchial epithelium has been previously shown to modulate its sensitivity towards microbial recognition by regulating receptor expression levels [112].…”
Section: Innate Immune Activation In Cf Lung Diseasementioning
confidence: 99%